Was It Possible to Stabilise the Price of Wool? Organised Wool Marketing 1916 to 1970. (1st August 2017) - Abbott, Malcolm; Merrett, David
Abstract : Wool is the only Australian commodity for which there has been an attempt to organise price stability through a buffer stock scheme (1970–91). Growers pressed for the introduction of a scheme since the early 1920s. We test the veracity of claims that the sale of the stockpiles optimised growers' returns. We also simulate the likely outcomes of the reserve price schemes (RPS) proposed in 1925 and 1952, respectively. Our findings are that post‐war stockpile disposals did not optimise wool growers' incomes, the undercapitalised proposed RPS of the 1920s would have collapsed in the depression, and that the post‐1952 RPS would have been in considerable difficulty.